2009
DOI: 10.1590/s0034-89102009005000069
|View full text |Cite
|
Sign up to set email alerts
|

Violências contra mulheres por parceiro íntimo em área urbana economicamente vulnerável, Brasília, DF

Abstract: High prevalences of violence show the magnitude of vulnerability and aggressions committed against women in relationships with intimate partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
16
1
34

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 13 publications
7
16
1
34
Order By: Relevance
“…Research indicates that the discovery of female infidelity intensifies violence against the woman by the partner. 23 The present study's results corroborate a study undertaken on the dynamics of domestic violence with 30 couples living in the south of Brazil, which revealed that suspicion of female infidelity acts as one of the biggest triggers for arguments and episodes of violence.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Research indicates that the discovery of female infidelity intensifies violence against the woman by the partner. 23 The present study's results corroborate a study undertaken on the dynamics of domestic violence with 30 couples living in the south of Brazil, which revealed that suspicion of female infidelity acts as one of the biggest triggers for arguments and episodes of violence.…”
supporting
confidence: 89%
“…The consumption of alcoholic drinks by the partners is one of the main causes leading the partner to commit crime. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Attention is also called to the fact that the women state that the use of drugs/alcohol is the event causing conjugal violence, it being considered that if this is absent, the conjugal relationship is healthier. The women studied declared that when their partners drink, they are transformed, attacking them, initially verbally, and then progressing to other types of violence.…”
mentioning
confidence: 99%
“…8 Essas repercussões para a saúde da mulher levam a uma maior procura por serviços de saúde, 9,10,16 portanto, cabe aos profissionais desses locais acolher e identificar a causa desse sofrimento. Na literatura encontra-se uma alta prevalência da violência contra a mulher, 3,7,23,24 Os achados deste estudo identificaram uma elevada prevalência de violência perpetrada por parceiro íntimo na população estudada, corroborando a literatura pertinente acerca dessa temática. O registro em prontuário foi realizado, majoritariamente, por médicos, seguido pelo registro por profissionais da enfermagem.…”
Section: Discussionunclassified
“…Considering their context of life, some said they could not rely on family support in any time, even on the case of a possible violence suffered. 17 In this context, the form of violence that presented the highest level was psychological violence throughout life -in the last year insults prevailed. In relation to physical violence, it was considerable the moderate values throughout life and in the last year, like pushing.…”
Section: Violence Against Women and Its Multiple Facesmentioning
confidence: 99%
“…It was also found the presence of sexual violence, once women had to do sex against their will -especially for fear of the partner. 17 The most frequent types of violence against women were the psychological, physical, and psychological accompanied by physical, being the psychological the most serious. The study results showed a high prevalence of partner violence -with women exposed to violence by their partner -and the most identified violence in the study was psychological, exceeding three times the physical violence and twice the sexual violence.…”
Section: Violence Against Women and Its Multiple Facesmentioning
confidence: 99%